ARTISTIC INTERPRETATION OF EPIC PLOTS IN UZBEK DRAMA (in the example of Usmon Azim’s dramas) - Shahnoza Qahhorova; Sattorova Mahliyo (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article general meaning of drama and artistic interpretation of epic plots in Uzbek drama are analyzed and the dramas by Usmon Azim are given and also analyzed as an example.